Human Peyer's patches: an immunohistochemical study. - Spencer, J (1986)
We have used immunoperoxidase techniques to characterise the Peyer's patches in human terminal ileum. The mantle zones of the B cell follicles in human Peyer's patches were surrounded by B cells which did not express surface IgD but which mostly expressed surface immunoglobulin of the IgM and/or IgA1 isotype. Few cells expressing surface IgG or IgA2 were detected. Cells with cytoplasmic immunoglobulin of all isotypes except IgD were present in the dome regions of the Peyer's patches as well as in the lamina propria. There was little evidence of traffic of immunoglobulin synthesising cells across the high endothelial venules. T cells were seen to surround the lymphoid follicles. They were most concentrated on the serosal aspect around the high endothelial venules. Cells with macrophage-like morphology were present in both the lamina propria and the dome region of the follicles; those in the lamina propria containing lysozyme and those in the dome region S100 protein. The results are discussed in relation to the generation and dissemination of antibody producing cells in human gut.